The successful visual artist: the building blocks of artistic careers model - Petrides, L.; Fernandes, A. (Journal of Arts Management, Law and Society, 2020)
This article examines career building for visual artists, whereby a successful career is defined as exhibiting work, reaching a wide audience, and making a living by selling art. Using insights from management, marketing, entrepreneurship, and sociology, the authors develop a conceptual model for constructing a successful career, the Building Blocks of Artistic Careers model (BBAC). Pursuing such a career entails entrepreneurial and marketing skills, cultivation of relationships with art world gatekeepers, brand creation strategies, and reputation management. The article contributes to the literature of visual arts entrepreneurship, has implications for art school curricula, and raises issues for further research.